2016
DOI: 10.15344/2456-351x/2016/118
|View full text |Cite
|
Sign up to set email alerts
|

Human Mercury Exposure Associated with Artisanal Gold Miners in Sudan

Abstract: Background: Mercury concentration in the blood is one of mercury exposure biomarkers. This study was conducted in Abuhamed mining area in Sudan, during the period from August 2012 to November 2014.The aim of the study was to evaluate serum mercury levels and to assess lung functions in artisanal gold miners. Methods: The study included 123 subjects, of them 83 were working in the gold mining area, beside 50 healthy volunteers from Khartoum State, as control group. Serum mercury was measured by direct mercury a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…This study showed that the Hugh level of mercury in urine sample taken from Altwahen area 12 km away from Abou Hamad in Nile river state (Sudan) (mean 2785.4238 ppm) and tremor 37%, which is different from the research done by global mercury project 13 . The study showed that the population's exposure did not lead to high mercury levels in blood, hair, or urine.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…This study showed that the Hugh level of mercury in urine sample taken from Altwahen area 12 km away from Abou Hamad in Nile river state (Sudan) (mean 2785.4238 ppm) and tremor 37%, which is different from the research done by global mercury project 13 . The study showed that the population's exposure did not lead to high mercury levels in blood, hair, or urine.…”
Section: Discussioncontrasting
confidence: 80%
“…This study is one of a few studies in Sudan aimed to evaluate the mercury toxicity among Sudanese people. Tayrab et al 13 , conducted a study in Abu Hamad and found a significant increase in serum mercury levels in the gold miners N, serum mercury level (1.40 ± 0.94 µg/L)). In our study, we agree that there is a significant increase in biological parameter urinate mercury level.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A few research studies have explored mercury exposure in ASGM and its associated health risks in Abu Hamad. One of the few studies highlighted elevated serum mercury levels among traditional gold miners from August 2012 to November 2014 [ 24 ]. Another study focused on urinary mercury concentrations in individuals occasionally exposed to mercury during artisanal gold mining, revealing alarming levels in 98% of participants [ 25 ].…”
Section: Introductionmentioning
confidence: 99%